DEFORMATION ANALYSIS WITH PSEUDO-STATIC ANALYSIS AND FREE â FIELD RACKING DEFORMATION METHOD DUE TO EARTHQUAKE: CASE STUDY JAKARTA MRT STATION - M.T. Sibagariang, Sarah
In designing the underground structure, it is necessary to evaluate the seismic load response to the structure. The evaluation carried out can be seen through the deformation that occurs in the structure. The deformation in the underground structure is influenced by the deformation in the soil (free-field). Deformation analysis was performed using pseudo-static analysis with Plaxis 2D and the freefield racking deformation method. First, a Site Specific Response Analysis (SSRA) was carried out using NERA and then continued with a structural deformation analysis. The analysis was carried out to determine the deformation that occurred by the five input motions of a 2500-year return period with earthquake subduction mechanisms and shallow crust. Based on the two analyzes carried out, the flexibility ratio of the results of the five input motions is smaller than one (F<1), which indicates that the deformation of the harmony station is relatively stiffer than that of the ground. In addition, F<1 shows that the surrounding soil is soft, by the results of the site class, namely soft soil (SE). It was found that the deformation of the structure using the racking freefield deformation method was more conservative than the deformation of the pseudo-static analysis.